Ethics Review in Anti-Doping Research: Experiences of Stakeholders. Issue 2 (2nd April 2020) - Devriendt, Thijs; Sanchini, Virginia; Borry, Pascal
Abstract: Background. The World Anti-Doping Agency is the international body coordinating anti-doping efforts, with the mandate of harmonizing anti-doping policy worldwide. With novel performance-enhancing compounds continuously entering the market, research is necessary to develop appropriate methods for their detection. WADA-accredited laboratories are required to spend 7% of their annual budget on this research and need to obtain ethics approval for studies involving human participants. Nevertheless, these labs may face difficulties in obtaining ethics approval for anti-doping research due to its distinct differences from traditional biomedical research. Therefore, our aim was to investigate potential difficulties in obtaining ethics approval for anti-doping research. Methods. Semi-structured interviews were conducted with stakeholders in anti-doping research to investigate their experiences toward the ethics review process of their research proposals. Interviews were transcribed, de-identified, coded and analyzed. Results. The interviews indicated that large discrepancies in the evaluation of anti-doping research proposals exist. A majority of the laboratories could not acquire ethics approval for the administration of substances not approved for medical use. Some laboratories faced obstacles to obtain ethics approval for substances approved for clinical use. Respondents communicated that ethics committees often lack background knowledge about the anti-doping context. Conclusions. Disapproval of research proposals may originate from concerns over the safety of the study, the fact that there is seldom a direct benefit to the participant, the consideration that volunteers may be incentivized to use prohibited substances, a lack of background knowledge about anti-doping, or the focus of research ethics committees on health research.